Face to Facebook: The relationship between social media and social travel. (30th September 2018) - Delbosc, Alexa; Mokhtarian, Patricia
Abstract: In an era of rapidly-expanding social media and smartphone use, there is much interest in understanding the impact that information and communication technology (ICT) can have on travel behaviour. In particular, some have conjectured that the prevalence of social media use among the millennial generation may be partially responsible for a shift away from car driving and toward more sustainable travel modes. This paper uses a purpose-designed survey to examine the relationship between physical and virtual social interaction. It quantified the frequency of interaction with members of one's social network through telephone, email, texting and social media and explored the association with face-to-face social interaction. Multiple regression and structural equation modelling revealed that in general, more frequent 'virtual' interaction was associated with more frequent face-to-face interaction, not less, even after controlling for income, age, gender, extroversion, and other covariates. The relationships differed in strength across different age groups; notably, social media interaction was only associated with face-to-face interaction amongst 18–29 year olds. This provides no evidence to support the hypothesis that social media use is reducing travel demand amongst the younger generation. Highlights: Interaction by social media associated with more frequent face to face interaction. Texting and social media more significant for young adults' social interaction. Phone contact significant for all age groups' social interaction. No evidence social media is replacing face to face interaction.